Mobilisasi Bibit Padi Unggul sistem Dapog antar Kabupaten Sebagai Alternatif Penyediaan Bibit Padi Guna Mendukung Percepatan Tanam Padi di Kalimantan Selatan - Abdul Sabur; Putu Sri Ratmini (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Sabur et al, 2016.Â Paddy Seed Superior mobilization Dapog system between the District as an Alternative Provision Paddy Seed to Support Accelerating Paddy PlantingÂ in South Kalimantan. JLSO 5(1):43-52.Breeding technology using dapog can be an alternative for the provision of rice seeds that can be mobilized anywhere even distances. In application required correct technique when the rolls of rice seeds will be moved so that no damage, and rice seeds can be used for optimal planting. The purpose of this study was conducted to determine the proper technique for memindahan seeds to great distances that use dapog seedlings, and to know which crop performance in mobilization after two weeks grown in paddy fields. This activity was conducted in August 2016, the nursery of paddy system dapog carried out in the village of Bungur New District of Tapin Central Tapin district, the rice seedlings were transferred to the village of Pangambau Hulu subdistrict Haruyan Hulu Sungai Tengah with the distance of 69 km and takes about 1 hour and 25 minutes to then directly planted in paddy fields that had been prepared. The research method with direct observations and describe. From the observation data obtained as follows, 230 rolls of seeds brought, 222 rolls can be directly planted using planting machines Jarwo trasplanter. In addition the level of damage to a minimum or an average of 1.5%, while the highest damage is due to wither due to the distance and wind by 2% or 5 rolls of a total of 230 scrolls were brought, and position rolls of rice seedlings that much gain exposure is positioned on top of the pile. Vibrations caused by road conditions are not smooth when seedlings in mobilization also occurred on a roll topmost ditumpukan seedlings, the number of rolls fall apart as much as 2% or 5 reels. The rolls are oppressed due stacked seed and seedlings were damaged due to errors at the time of rolling 1%. Placements are set up well during the trip, and experienced technical personnel, making seed rolls only minimal shifting. Mobilization time better morning and the movement speed of the car attempted stable with an average speed of 40-60 km / h on a smooth path to reduce wind into rolls seed and on the bumpy roads the speed reduced to 10-20 km / h or adjust to the road conditions so that the vibration can be minimized.